EKSISTENSI TRADISI JUADAH DALAM MELESTARIKAN SOLIDARITAS DALAM UPACARA PERKAWINAN (Studi di Korong Kampung Ladang Kabupaten Padang Pariaman) - Fardayanti, Yanti; Nurman, Nurman (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2013)
Juadah is a tradition in the traditional wedding ceremony in Minangkabau tradition from West Sumatera. This research aims to analyse the juadah tradition in maintaining solidarity in the Kampung Ladang Korong small village wedding ceremony. This research is qualitative using in-depth interview, observation, and documentation study to obtain data. Sources interviewed were selected by purposive sampling. The result shows that the juadah is still commemorated in the research site. This tradition’s purpose is to maintain solidarity in social binding including families and communities. This tradition also grow the spirit of gotong royong (solidarity works) although modernisation has changed some of its implementation. Key words: juadah tradition, Minangkabau wedding ceremony, social solidarity